Farmers' participatory site specific nutrient management in gangetic tidal floodplain soil for high yielding boro rice (Oryza Sativa L.) - Nath, D.K.; Haque, F.; Amin, F.; Islam, M. Sh; Saleque, M.A. (Bangladesh Academy of Sciences, 2013)
Site Specific Nutrient Management (SSNM) trials were conducted for irrigated, transplanted and high yielding rice (Oryza sativa L.) during Boro season 2012. Four treatments (NPK, PK, NK, and NP) were applied in a randomized complete block design to assess the effects of indigenous nutrient elements on rice yield and yield components. The trials were conducted so as to develop a site specific nutrient management approach for the farmers of Gangtic Tidal Floodplain ecosystem. The highest grain-yield of 5.64 t ha-1 was observed in NPK treatment, which gave 9.0, 34.4 and 50.7% higher yields than those of NP, NK and PK, respectively. The response to indigenous K was remarkable and it gave the second highest yield (5.13 t ha-1). The yield response to indigenous N was very poor and the lowest yield was found in N omission treatment (2.78 t ha-1). The response to indigenous P was also poor (3.7 t ha-1). This result shows that nitrogen and phosphorus are the most vibrant factors to increase yield since omission of N and P had significant impact on yield during Boro season. Use of N, P and K at 128.7, 8.08 and 12.78 kg, respectively could be recommended for growing BRRI dhan47 in Boro season. It could save P and K nutrient by 55.11 and 75.89 % compared to that of NPK treatment, respectively. DOI: http://dx.doi.org/10.3329/agric.v11i1.15236 The Agriculturists 2013; 11(1) 8-14